Evaluating Pennsylvania Pharmacists' Provision of Community-based Patient Care Services - Maria A. Osborne (INNOVATIONS in Pharmacy, 2011)
Objective: To identify and describe Pennsylvania pharmacists who currently provide or are interested in providing community-based patient care services and are interested in joining a statewide practice network.